Correlation between heavy metals and polyaromatic hydrocarbons of particulate matter in the flue gas of municipal solid waste incinerators in north Vietnam - Pham Viet Quoc,; Nguyen Thi Hue,; Nguyen Thi Phuong Mai,; Le Phuong Thu, (Vietnam Journal of Science and Technology, 2023)
This study aimed to determine the content of heavy metals (Cu, Ni, Pb, Zn, Cd, Cr, and As) and polyaromatic hydrocarbon (PAHs), and focus on their relationship in particulate matter (<10μm) contained in the flue gas of the incinerators. Samples were collected in the exhausted gas of 5 municipal solid waste incinerators located in Bac Giang, Bac Ninh, Hai Duong, Hanoi, and Hai Phong. Heavy metals and PAHs were analyzed by ICP-MS and GC-MS, respectively. The heavy metal content shows a significant difference between incinerators, varying from 0.822 to 6.13 × 103 µg/Nm3. In which, the predominant element in the PM10 samples was zinc, accounting for 80% of the total content of studied elements, it was mixed with Pb and Cu (10 to 20%). The contribution of Cd was stable at roughly 5% of the total heavy metal content. Meanwhile, total polyaromatic hydrocarbon exhibited a fairly low concentration, varying from 21.9 to 994 µg/Nm3, of which PAHs have the carcinogenic potential ranging from 21.3 to 73.2% of total PAHs. These results hypothesized the correlation between Zn and Pb to the formation of PAHs during the combustion and discharge to the environment through waste dust. However, the low molecular PAH content decreased when heavy metal concentration increased.